Increasing Antenatal Care and HIV Testing among Rural Pregnant Women with Conditional Cash Transfers to Self-Help Groups: An Evaluation Study in Rural Mysore, India. (1st September 2013) - Madhivanan, Purnima; NiranjanKumar, Bhavana; Shaheen, Reshma; Jaykrishna, Poornima; Ravi, Kavitha; Gowda, Savitha; Srinivas, Vijaya; Arun, Anjali; Krupp, Karl
Abstract : Background . We describe a one-year evaluation study comparing SCIL intervention of mobile provision of integrated ANC/ HIV testing with an enhanced (SCIL+) intervention of community mobilization strategy providing conditional cash transfers (CCT) to women's SHG for identifying and accompanying pregnant women to mobile clinics. Methods . Twenty pairs of villages matched on population, socioeconomic status, access to medical facilities, and distance from Mysore city were divided between SCIL and SCIL+ interventions. The primary study outcome was the proportion of total pregnancies in these villages who received ANC and HIV testing. Results . Between April 2011 and March 2012, 552 pregnant women participated in SCIL or SCIL+ interventions. Among women who were pregnant at the time of intervention delivery, 181 of 418 (43.3%) women pregnant at the time of intervention delivery received ANC in the SCIL arm, while 371 of 512 (72.5%) received ANC in the SCIL+ arm (P < 0.001 ); 175 (97%) in the SCIL and 366 (98.6%) in the SCIL+ arm consented to HIV testing (P < 0.001 ). HIV prevalence of 0.6% was detected among SCIL clinic, and 0.9% among attending SCIL+ clinic attendees. Conclusion . Provision of CCT to women's microeconomic SHG appears to significantly increase uptake of ANC/HIV testing services in rural Mysore villages.